Mortalidade por suicídio no Paraná : tendência e distribuição epidemiológica - Rosa, Natalina Maria da (2015)
Current study analyzes the trend and the epidemiological distribution of aspects related to suicide methods in the state of Paraná, Brazil, from 1996 to 2012, with regard to gender, age, schooling, marital status, place of occurrence and local health service. Mortality data were obtained from the Mortality Data System and analyzed by categories following the Tenth International Classification of Diseases, namely, "self-intoxication by pesticide" (X68); "?hanging" (X70); "firearms" (X72-X75) and "other methods" (X60-X67, X69, X71, X76-X84). Data were grouped into four periods - 1996 to 2000; 2001 to 2004; 2005 to 2008; 2009 to 2012 - to analyze mortality trends by suicide, and statistically analyzed by polynomial regression models. For the epidemiological distribution of aspects related to suicide method, data were grouped into two periods - 1996 to 2000 and 2009 to 2012, whilst descriptive and inferential statistics analysis was performed by the x2 test and association measure with Odds Ratio. Health Macroregions and 63.6% of Health Regional Units revealed decreasing trends in mortality rates by suicide, with the exception of the Eastern Macroregion at the First Health Regional Unit (Paranaguá) with revealed increasing trends. There was also a decreasing trend in deaths by suicide for both genders, even though males still have an average higher rate than females (13.8 and 3.3 for 100000 inhabitants, respectively). There was also a decrease in the death rates by suicide in males in the Eastern Macroregion at the 2nd Regional Health Unit (Metropolitan area) (r2 = 0.81; p<0.001) and in the Northwestern Macroregion at the 12th Regional Health Unit (Umuarama) (r2 = 0.76; p<0.001). The western region of the state of Paraná had the highest rate (β0 = 19.3) among the Macroregions. In the case of females, there was a decrease for the Northern Microregion for the 17th Regional Health Unit (Londrina) (r2 = 0.96; p<0.001). A decrease was also reported in over 65-years-old males, contrastingly to females between 15 and 44 years and between 45 and 64 years. Higher mortality rates by suicide occurred between 1996 and 2000 for males and females (<15 and 5 deaths in 100000 inhabitants, respectively). Death by hanging increased between 1996 and 2000 and between 2009 and 2012, whereas an association between males and <45 years was detected between 1996 and 2000. During the 2009-2012 period, males were associated with <12-year schooling, single, at home. The Western Macroregion revealed higher mortality rates by method of suicide. Results provide relevant tools for the monitoring of mortality by suicide since they furnish means for the implementation of intersectorial activities/strategies. Data may also contribute for the upgrading of health professionals in the identification of potential suicides, aiming at a more drastic decrease in deaths by suicide in the state of Paraná.